1999
DOI: 10.2134/jeq1999.00472425002800050009x
|View full text |Cite
|
Sign up to set email alerts
|

Phytoaccumulation of Trace Elements by Wetland Plants: III. Uptake and Accumulation of Ten Trace Elements by Twelve Plant Species

Abstract: Interest is increasing in using wetland plants in constructed wetlands to remove toxic elements from polluted wastewater. To identify those wetland plants that hyperaccumulate trace elements, 12 plant species were tested for their efficiency to bioconcentrate 10 potentially toxic trace elements including As, B, Cd, Cr, Cu, Pb, Mn, Hg, Ni, and Se. Individual plants were grown under carefully controlled conditions and supplied with 1 mg L−1 of each trace element individually for 10 d. Except B, all elements accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
65
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(79 citation statements)
references
References 0 publications
12
65
0
2
Order By: Relevance
“…Accumulators have been reported in Gramineae family such as Leersia hexandra (Zhang et al, 2007) or Miscanthus sinensis (Arduini et al, 2006). High accumulations of Cr have been described in other species as Salsola kali (Gardea-Torresdey et al, 2005), Convulvulus arvensis (Gardea-Torresdey et al, 2004), Polygonum hydropiperoides (Qian et al, 1999) Glycine max and Helianthus annuus (Mei et al, 2002), Azolla caroliana (Bennicelli et al, 2004) and Propopsis spp (Aldrich et al, 2003). Genotypic differences in Cr uptake have been found in Indian mustard (Diwan et al, 2008) and rice (Zeng et al, 2010).…”
Section: Effect Of Genotype Cr(iii) and Cr(vi) On Plant Growth And Mmentioning
confidence: 99%
“…Accumulators have been reported in Gramineae family such as Leersia hexandra (Zhang et al, 2007) or Miscanthus sinensis (Arduini et al, 2006). High accumulations of Cr have been described in other species as Salsola kali (Gardea-Torresdey et al, 2005), Convulvulus arvensis (Gardea-Torresdey et al, 2004), Polygonum hydropiperoides (Qian et al, 1999) Glycine max and Helianthus annuus (Mei et al, 2002), Azolla caroliana (Bennicelli et al, 2004) and Propopsis spp (Aldrich et al, 2003). Genotypic differences in Cr uptake have been found in Indian mustard (Diwan et al, 2008) and rice (Zeng et al, 2010).…”
Section: Effect Of Genotype Cr(iii) and Cr(vi) On Plant Growth And Mmentioning
confidence: 99%
“…Phytoremediation technology, especially rhizofiltration, has encouraged many researchers to investigate the potential of different aquatic plant species for removal of toxic elements such as B, Cr, Cu, Hg, Cd, Ni, Se and As from bodies of water (Zayed et al, 1998;Qian et al, 1999;Zhu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…followed by Salvinia natans L. 6295 mg/kg DW. Most emergent wetland plant species, however, showed lower Ni accumulation than floating species: for example cattail had low root Ni concentrations of 1000 mg/kg DW and shoot concentrations of 400 mg/kg DW (Qian, et al, 1999) and watercress had an all of the plant Ni concentration of 350 mg/kg DW. In the pots receiving the highest level of zinc in the nutrient solution (600 µg/g Zn), the roots contained a mean concentration of about 10 000 µg/ g Zn in the dry root tissue, while the tops contained about 1000 µg/g Zn.…”
Section: Discussionmentioning
confidence: 98%
“…However, water pollution by heavy metals has only become acute in recent years because metal ions from natural, domestic and industrial sources tend to concentrate in the organic residue at the sewage treatment works. Several studies have shown that constructed wetlands are very effective in removing heavy metals from polluted wastewaters (Qian, et al, 1999). Different wetland plant species differ, however, in their abilities to take up and accumulate various trace elements in their tissues .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation